Black Hole Accretion and Spin-up through Stellar Collisions in Dense Star Clusters - Fulya Kıroğlu; Kyle Kremer; Sylvia Biscoveanu; Elena González Prieto; Frederic A. Rasio (The Astrophysical Journal)
Dynamical interactions in dense star clusters could significantly influence the properties of black holes, leaving imprints on their gravitational-wave signatures. While previous studies have mostly focused on repeated black hole mergers for spin and mass growth, this work examines the impact of physical collisions and close encounters between black holes and (noncompact) stars. Using Monte Carlo N -body models of dense star clusters, we find that a large fraction of black holes retained upon formation undergo collisions with stars. Within our explored cluster models, the proportion of binary black hole mergers affected by stellar collisions ranges from 10%–60%. If all stellar-mass black holes are initially nonspinning, we find that up to 40% of merging binary black holes may have components with dimensionless spin parameter χ  ≳ 0.2 because of prior stellar collisions, while typically about 10% have spins near χ  = 0.7 from prior black hole mergers. We demonstrate that young star clusters are especially important environments, as they can produce collisions of black holes with very massive stars, allowing for significant spin-up of the black holes through accretion. Our predictions for black hole spin distributions from these stellar collisions highlight their sensitivity to accretion efficiency, underscoring the need for detailed hydrodynamic calculations to better understand the accretion physics following these interactions.